Alpha-synuclein activates BV2 microglia dependent on its aggregation state - Hoffmann, Alana; Ettle, Benjamin; Bruno, Ariane; Kulinich, Anna; Hoffmann, Anna-Carin; von Wittgenstein, Julia; Winkler, Jürgen; Xiang, Wei; Schlachetzki, Johannes (Biochemical and Biophysical Research Communications, 2016)
Synucleinopathies such as Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA) are defined by the presence of intracellular alpha-synuclein aggregates in neurons and/or oligodendrocytes. In addition, post mortem tissue analysis revealed profound changes in microglial morphology, indicating microglial activation and neuroinflammation. Thus, alpha-synuclein may directly activate microglia, leading to increased production of key pro-inflammatory cytokines like tumor necrosis factor-alpha (TNF-?) and interleukin-1beta (IL-1?), which in turn modulates the disease progression. The distinct alpha-synuclein species, which mediates the activation of microglia, is not well defined. We hypothesized that microglial activation depends on a specific aggregation state of alpha-synuclein. Here, we show that primarily human fibrillar alpha-synuclein increased the production and secretion of pro-inflammatory cytokines by microglial BV2 cells compared to monomeric and oligomeric alpha-synuclein. BV2 cells also preferentially phagocytosed fibrillar alpha-synuclein compared to alpha-synuclein monomers and oligomers. Microglial uptake of alpha-synuclein fibrils and the consequent activation were time- and concentration-dependent. Moreover, the degree of fibrillization determined the efficiency of microglial internalization. Taken together, our study highlights the specific crosstalk of distinct alpha-synuclein species with microglial cells.
EVALuna2:4715